Coronaridine congeners decrease neuropathic pain in mice and inhibit α9α10 nicotinic acetylcholine receptors and CaV2.2 channels. (15th September 2020) - Arias, Hugo R.; Tae, Han-Shen; Micheli, Laura; Yousuf, Arsalan; Ghelardini, Carla; Adams, David J.; Di Cesare Mannelli, Lorenzo
Abstract: The primary aim of this study was to determine the anti-neuropathic activity of (±)-18-methoxycoronaridine [(±)-18-MC] and (+)-catharanthine in mice by using the oxaliplatin-induced neuropathic pain paradigm and cold plate test. The results showed that both coronaridine congeners induce anti-neuropathic pain activity at a dose of 72 mg/kg ( per os ), whereas a lower dose (36 mg/kg) of (+)-catharanthine decreased the progress of oxaliplatin-induced neuropathic pain. To determine the underlying molecular mechanism, electrophysiological recordings were performed on α9α10, α3β4, and α4β2 nAChRs as well as voltage-gated calcium (CaV 2.2) channels modulated by G protein-coupled γ-aminobutyric acid type B receptors (GABAB Rs). The results showed that (±)-18-MC and (+)-catharanthine competitively inhibit α9α10 nAChRs with potencies higher than that at α3β4 and α4β2 nAChRs and directly block CaV 2.2 channels without activating GABAB Rs. Considering the potency of the coronaridine congeners at Cav2.2 channels and α9α10 nAChRs, and the calculated brain concentration of (+)-catharanthine, it is plausible that the observed anti-neuropathic pain effects are mediated by peripheral and central mechanisms involving the inhibition of α9α10 nAChRs and/or CaV 2.2 channels. Graphical abstract: Image 1 Highlights: (±)-18-MC and (+)-catharanthine decrease drug-induced neuropathic pain. Both drugs inhibit α9α10 at higher potency than that for α3β4 and α4β2 nAChRs. Both drugs directly inhibit CaV 2.2 channels but not via activation of GABAB R. Their analgesic mechanisms may involve the inhibition of α9α10 nAChRs and/or CaV 2.2 channels.